AB0138 The bone marrow oedema is linked to a osteoclastic environment in bone marrow during collagen induced mice arthritis development. (12th June 2018) - Tan, W.; Xuan, W.; Wu, Q.; Luo, A.; Yan, W.; Wang, F.
Abstract : Background: Bone erosion is a central pathogenic event in Rheumatoid arthritis (RA) and is associated with joint damage and poor functional outcome. The synovitis is traditionally regarded as the primary event of bone erosion in RA and synovial cells are usually thought to play a critical role in this pathologic process. However, the synovitis-centred concept has long been challenged by recent clinical finds. Bone erosion formation also could be found in joints without clinical traits of synovitis, suggesting that synovitis and joint erosion could be uncoupled. Moreover, recent study demonstrated that bone marrow oedema (BME) that identified by magnetic resonance imaging (MRI) is strongly associated with erosive progression, which independent of local synovitis in RA. Objectives: BME is also called osteitis, which represent the replacement of adipose tissue with inflammatory cells in bone marrow. In this study we addressed 2 questions: 1) the course of BME and synovitis in a same joint during CIA development; 2) how BME cause the bone erosion in CIA. Methods: Using collagen induced mice arthritis model, we compared the compared the time course of appearance of BME, synovitis and arthritic symptoms during the development of CIA. The changes RANKL, cytokines, osteoclast and immune cells expression in bone marrow during the development of CIA were analysed by flow cytometric analysis, immunofluorescence staining and RT-qPCR. Results: MRI BME can be identified as early as 25 days after first immunisation, when there is no any histopathological changes and arthritis symptoms. Flow cytometry and immunofluorescence staining indicated that the proportion of pre-OCs were significantly increased in bone marrow after day 25 with the presence of BME. At day 25, accompanied by presence of BME and increased pre-OCs, the number of trabecular bone was significantly diminished as compared with those at day 20 and reached its lowest number at day 35. We then examined the transcription of several pro-inflammatory cytokines and chemokines related to OCs differentiation, migration and activation, such as RANKL, IL-17, TNFa, CCL3, CCL4, CCL12, CCR5 by Real-time PCR. The most prominent RANKL change was observed at day 35. IL-17 and TNFa mRNA were elevated from day 25, reaching a peak at day 28 and thereafter gradually decreasing. Expression of CCL3 and CCL12 were only higher at day 28 and day 25, respectively, while there was no significant change in CCR5 and CCL4 mRNA in the bone marrow. The proportion of T cells and monocytes in bone marrow were significantly higher from day 25 to day 45. No differences in B cells and plasma cells were detectable at any time points. Bone marrow cells from the presence of BME showed significantly increased ability to formation OCs in vitro . Conclusions: BME precede the synovitis and arthritic symptoms during the development of CIA. Accompanied BME appearance, we identified an altered bone microenvironment that favours OCs differentiation and survival in CIA mice. We proposed that BME linked to a unique "osteoclastic environment" in CIA disease progression. These findings provide a new perspective for comprehending the development of erosions in RA. Disclosure of Interest: None declared